Cardiothoracic Ratio of "Normal" Newborn Babies - W. T. Karjomanggolo; L. A. Tamaela; H. E. Monintja (Paediatrica Indonesiana, 1974)
The present paper deals with the measurement of the transverse diameter of the heart and the cardiothoracic ratio in "normal" newborn babies on the first day of life. A comparison has beeru made on the fourth day.